A child with pheochromocytoma and malignant hypertension - Abidin S.; Alatas H.; I. G. N Wila Wirya; Taralan Tambunan (Indonesian Pediatric Society, 1981)
Herein we report a boy of 13 years old who suffered from pheochromocytoma with malignant hypertension. No metastasis was found and surgical approach was done successfully. Histopathologic examination showed pheochromocytoma of the left suprarenal gland with pleomorphism in the primary tumor.Postoperatively the blood pressure returned to normal within one month and remained so within 3 years follow up.